2015
DOI: 10.1111/iju.12834
|View full text |Cite
|
Sign up to set email alerts
|

Transumbilical laparoendoscopic single‐site surgery versus conventional laparoscopy for the resection of retroperitoneal paragangliomas

Abstract: Objectives: To compare transumbilical laparoendoscopic single-site surgery with conventional laparoscopy for the resection of retroperitoneal paragangliomas. Methods: In the present case-control study, we compared 11 transumbilical laparoendoscopic single-site surgery procedures with 22 conventional laparoscopy procedures carried out to treat retroperitoneal paragangliomas between June 2004 and October 2013 at Peking Union Medical Hospital, Beijing, China. Operative time, estimated intraoperative blood loss, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Some reports have indicated that the retroperitoneal approach shortens the surgical duration 32,33 . In addition, reports also exist on the single‐site and robotic surgeries 34,35 …”
Section: Discussionmentioning
confidence: 99%
“…Some reports have indicated that the retroperitoneal approach shortens the surgical duration 32,33 . In addition, reports also exist on the single‐site and robotic surgeries 34,35 …”
Section: Discussionmentioning
confidence: 99%
“… 14 In properly selected patients, transumbilical single‐port laparoscopic surgery can be used for retroperitoneal paragangliomas. 15 Here, transumbilical plus two‐port laparoscopic surgery was selected for safety because of the challenging nature of the aortocaval paraganglioma.…”
Section: Discussionmentioning
confidence: 99%